BSCI-12. COMPREHENSIVE GENOMIC ANALYSIS OF BRAIN METASTASES FROM MULTIPLE CANCER TYPES. (12th August 2019) - Fukumura, Kazutaka; Mao, Xizeng; Song, Xingzhi; Fischer, Grant; Yang, Jie; Sulman, Erik; Davies, Michael; Zhang, Jianhua; Huse, Jason
Abstract: PURPOSE: Brain metastases occur in approximately 8–10% of patients with cancer, and the incidence has increased over the past decades. The most common primary tumors responsible for brain metastases are lung cancer, melanoma, renal cell carcinoma (RCC), breast cancer and colorectal cancer. The precise mechanisms by which genomic and transcriptional abnormalities drive the formation of brain metastases remain unclear. Here, we conducted comprehensive genomic and transcriptional analysis with paired primary tumor tissue (or extracranial metastasis tissue) and brain metastasis tissue using whole-exome sequencing (WES), mRNA-Seq and global methylation profiling. METHODS: Frozen, paired brain metastasis tissue and primary tumor tissue (or extracranial metastasis tissue) and white blood cells were acquired from RCC (n=12), breast cancer (n=17), lung cancer (n=15) and melanoma (n=14) patients, followed by extraction of DNA and RNA. WES and mRNA-Seq were performed on the Illumina HiSeq4000 platform. For methylation profiling, DNA was analyzed using Illumina Infinium MethylationEPIC Beadchip arrays. RESULTS: Somatic mutations or methylation of VHL gene were identified in 81.8% of RCC patients. Gene Set Enrichment Analysis revealed significant enrichment for hypoxia pathway transcripts in RCC brain metastases relative to primary tumors. The most common alterations in breast and lung cancer patients were TP53 mutations with frequencies of 50.0% and 73.3%, followed by ERBB2 alterations (43.8%) in breast cancer patients and mutually exclusive alterations of EGFR (33.3%) and KRAS (26.7%) in lung cancer patients. Mutually exclusive alterations of NRAS (42.9%) and BRAF (42.9%) were also observed in melanoma patients. Gene expression and epigenetic analysis revealed characteristics of brain metastases depending on primary cancer types. CONCLUSIONS: Comprehensive genomic analysis of brain metastases from four different cancer types revealed that brain metastasis tissues have unique genomic, transcriptional and epigenetic profiles according to histopathology groups. Therefore, the therapeutic strategies should be designed based at least in part on tumor histiogenesis.